State Administration of Retirement Age in the terms of Budget Crisis - A. K. Solovyev (Управление)
The aim of the study is to analyze the effect of age on the appointment of the state pension fiscal system in our country.The problem of rising of the retirement age in Russia is given a value that is far away from the traditional context of direct influence of demographic processes on the level of pensions, on the one hand, and adaptation of the pension system to changing demographic factors, on the other.In the article the pension system for the first time is considered as a multifactorial model that corrects the degree of dependence on the mutually complex of macroeconomic and demographic factors in the different historical periods. This requires a fundamental change in the methodological approaches to the problem of rising the retirement age by using actuarial methods of forecasting.Actuarial analysis of the problem of retirement age in the work shows that the perception of the linear dependence of the age of the destination state of the demographic parameters cannot be considered as a tool for regulating the efficiency of the pension system.The results of the study are the specific parameters of actuarial assessments of the impact of demographic and macroeconomic conditions to increase the retirement age in Russia, conducted using data from the state statistics, formulated practical proposals to mitigate negative economic consequences.Conclusion: Rising the retirement age should be aimed at economic stimulation of formation of the pension rights of the insured in the long term, rather than the economy of the state budget. Methodological approaches, grounded in the work, and quantitative results of the actuarial calculations will be used in the formation of public pension policy in the preparation of the regulations to rise the retirement age, the pension formula of calculating the pension rights of insured persons, the mechanism of pension indexation.